Shock veins in the Sahara 02500 ordinary chondrite - Owocki, Krzysztof; Muszyński, Andrzej (Wydawnictwo Naukowe UAM, 2012)
A specimen of the Sahara 02500 ordinary chondrite contains shock-produced veins consisting of recrystallised fine- grained pyroxenes that include small droplets of Ni-rich metal. Non-melted olivines and pyroxenes show planar deformations filled by shock-melted and -polluted metal and troilite. Shock-melted feldspathic glass is present close to the shock veins. Geothermometric estimations indicate that the meteorite locally experienced moderate shock metamorphism with a minimum local peak temperature above 1400ºC, resulting in partial melting of Ca-poor pyroxene and full melting of feldspars, metal and sulphides. The mineral assemblage in the shock veins suggests a pressure during melt recrystallisation below 10 GPa.
Keywords: Ordinary chondrite; Shock veins; Subsolidus recrystallization